2023
DOI: 10.1123/pes.2021-0188
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and Biomarkers Among Children and Adolescents With Sickle Cell Disease

Abstract: Background: Sickle cell disease is the most common genetic hemoglobinopathy globally and systemically affects body functioning, decreasing exercise capacity. Objective: To assess exercise capacity through the 6-minute walk test (6MWT) and biomarkers in children and adolescents with sickle cell disease. Materials and Methods: Cross-sectional study involving 20 children and adolescents from Brazil. Demographic and socioeconomic data were obtained. Baseline measurements included biomarkers (red blood cells, hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Hostyn et al 3 showed a higher number of hospitalizations in children and adolescents who walked a shortened distance. Patients with SCA have impact on the distance walked at the 6‐min walk (6MWT) test associated with inflammatory levels 6 and cardiovascular impairment 7 . Additionally to the 6MWT, the Modified Shuttle Test (MST) is an alternative to assess exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Hostyn et al 3 showed a higher number of hospitalizations in children and adolescents who walked a shortened distance. Patients with SCA have impact on the distance walked at the 6‐min walk (6MWT) test associated with inflammatory levels 6 and cardiovascular impairment 7 . Additionally to the 6MWT, the Modified Shuttle Test (MST) is an alternative to assess exercise capacity.…”
Section: Introductionmentioning
confidence: 99%